From Moscow to Baghdad : Studies on Middle Eastern Christianity in Memory of Nikolai Seleznyov - Loesov, Sergey; Minov, Sergey; Treiger, Alexander (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
From Moscow to Baghdad is a collection of studies on the history and culture of Middle Eastern Christian communities, Semitic linguistics, and related topics, dedicated to the memory of Prof. Dr. Nikolai Seleznyov (1971-2021), Leading Research Fellow at the Institute for Oriental and Classical Studies, National Research University Higher School of Economics, Moscow and a prominent scholar of Syriac and Christian Arabic literature. In this volume Nikolai's friends and colleagues present their finest research, including editions and translations of previously unpublished texts. The subjects range from Second-Temple Jewish pseudepigrapha to late antique hagiography, Syriac and Arabic Christianity, Christian-Muslim relations, and Neo-Aramaic dialects.